(3CQHYhf MOjkKG aj GdMK Ydi EUWfGY GdeYQhas
(3ChdgG (B:s
(3GdMeO ddg eZjK ef ESJZGK Hg hGSJfO Edjg hHYO agPg CQHYhf MOjKkG ai GdMK Ydi EUWfGY GdeYQha hbVGA GdMGLI Gdedgha fbdgG WGFaI ef GdeMOKjf hQhGgG LeGYI ef GdYdeGA GdeYJHQjf s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3cdce QGY heSFhd Yf QYjJg GdEeGe QGY heSFhd Yf QYjJg hGdeQCI QGYjI ai HjJ RhLgG heSFhdg Yf QYjJgG hGdNGOe QGY ai eGd SjOg heSFhd Yf QYjJg hcdce QGY heSFhd Yf QYjJg (B) (3hGdMeO ddg hMOg hUdi Gddg Ydi ef dGfHi HYOs
(3HgG fXGe GdJYbjHIs
(3HBNQg eWGdYI HGSe jhSa Hf OGeGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs